Contribution of peer instruction in understanding knowledge in morphology classes for Medicine students (Research, Society and Development, 2022)
The objective will be to analyze from the literature how the Peer Instruction (PI) technique can increase the performance and understanding of students in morphology classes. Qualitative, exploratory and interventionist research. The research will be in the morphology classroom, at the Faculty of Medicine - Centro Universitário Integrado, Campo Mourão - PR. Students will be in the sixth period of medicine. The estimated sample will be 80 students. Initially, an expository class will be administered with the help of powerpoint, and after applying questions based on clinical cases regarding the subject already taught, by the Socrative Student platform. Students will answer the multiple choice questions individually, after discussing among themselves why they chose this alternative without knowing the correct answer. The same will be reapplied to evaluate the income gain. Data collection will be carried out through a questionnaire. The questions will be open for participants to express themselves freely. For the analysis, the Iramuteq software will be used. The IP has been adopted as an alternative for collaborative learning, being considered a teaching method that aims at greater interaction between students during classroom discussions, providing a space for arguments and relationships between students. In this perspective, the diversity of results found shows that the IP is a highly recommended proposal, especially when seeking to engage the student in the learning process. It is believed that the PI can be a timely intervention to develop skills and abilities during morphology classes.